Design and Fabrication of Hairpin Bandpass Filter with Square Shaped Defected Ground Structure - Misra, Apurva; Kumar, Manish (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2019)
In this paper, the design and simulation of microstrip hairpin bandpass filter with square shaped defected ground structure is described. The method used to design the filter was very efficient and requires less effort. The filter was designed and then simulated on HFSS tool and the results were verified by the fabrication and testing process. The fabrication was performed on the material GaAs The proposed bandpass filter with a square shaped defected ground structure has good performance. The proposed hairpin bandpass filter showed the return loss of -14.69dB at 4.2 GHz, -14.97 dB at 4.8 GHz, and - 19.15 dB at 5.6 GHz, -17.13dB at 6.5GHz, -13.7dB at 7.3 GHz. The insertion losses with square shaped defect were 0.8dB/0.3dB/0.16dB/0.8dB/1.4dB. 3dB and the bandwidth of proposed bandpass filter is 700 MHz/ 150 MHz/ 200 MHz /100 MHz/and 85 MHz at the center frequencies of 4.2 GHz/4.8 GHz/ 5.6 GHz/ 6.5GHz/ 7.3 GHz. In this work, the area has been reduced by 33%.